STRUKTUR CERITA RAKYAT BUGIS CENRANA AJU MADDARA TAU (PENDEKATAN ANTROPOLOGI SASTRA) (Structure of Buginese Folktale Cenrana Aju Maddara Tau (an Antropological Literary Approach) - Hasina Fajrin R Ummu Fatimah Ria Lestari (Balai Bahasa Sumatra Barat, 2016)
This research discusses about the structure of Buginese folklore Cenrana Aju Maddara Tau by antropological literary approach. The purposes of this research are 1) to describe the stuctureand content of Cenrana Aju Maddara Tau folktale; 2) to talk the Buginese culture in Cenrana Aju Maddara Tau folktale. The oral literature as Cenrana Aju Maddara Tau folktale, can beanalyzed by two perspectives, as a fiction and as a culture artefact. As a fiction, structuralism theory was used for analyzing about its characters, theme, settings, plot, and point of view inthe story. On the other hand, as a culture artefact, it was analyzed by antropological literary. Its results, as structurally, Cenrana Aju Maddara Tau folktale composed by characters, theme, settings, plot, and point of view. As antropological literary approach, by that story we can know about Buginese people antropologically.